(untitled) (Fiep Bulletin - online, 2014)
ABSTRACT: This study one becomes viable for the sum of elucidating the symbolic aspects gifts in the imaginary one of the blind practitioners in passage of open sea and to go deep, in the imaginary theoretical bias of the social one, what it stimulates the human being to launch itself the sea, a wild environment, whose references are the voice and the touch of the partner-guide. The absence of the guide makes impracticable the participation of the athlete in the test, being this source of reference, ability technique, volunteer, its eyes, its proper extension, but also obstacle, the stranger. The guide represents the cane, is the mediating object of the communicability with the environment, that one that facilitates the ticket to it, the cooperator without bond of complicity. It is a qualitative and exploratory study with eight blind people of the Institute Benjamin Constant, passages in opened waters, using half-structuralized interviews and Allegories of the Animals, allowing to formulate dreams projective of the ideals of pulses. He aims at to understand the directions of this adventure, orientation and corporal mobility, explicated the world of the significances that constitute Imaginary the Social one of these swimmers, detaching some express symbolic elements in the speeches. Practicing blind people of sports exercise, beyond the physical activity, the right to go and to come with independence and autonomy. He is in the exercise of this practical that with freedom, they dare and they defy its conditions of deficient. Reborn heroically of waters of the sea, searching forces overcoming, conquest that seem to obtain in the inclusive perspective, to face the social discrimination. Interpreting the results we detect three animals: the dog has function of psychopigeons, clarifying, guide, seers . The dolphins regeneration, reminding, wisdom, prudence, displacement, gentleman of the navigation. The flight of the bird establishes relations between sky and land, release, omen, message of the sky, the slightness. The adventure in the sea allow-in understanding them this imaginary, where water is life, appearing of the darknesses, being rehabilitated. They are moved for symbols of seeing, force, overcoming and conquest.